Student Academic Monitoring and Support in Higher Education: A Systems Thinking Perspective (Journal of Student Affairs in Africa, 2021)
This article interrogates an Academic Monitoring and Support system (AMS), which was designed to enhance first-year student progression at a South African University. Institutional research evidence produced through engagement with AMS practitioners and university leadership, analysed through thelens of Systems Thinking, reveals a well-intentioned system, whose efficacy is compromised by systemic incoherence. The data suggests that loosely defined roles and responsibilities of AMS practitioners, their level of preparedness to provide academic support, their conditions of employment and job profiles,all act in concert to compromise the intended outcomes of the programme. The authors contend that opportunities do exist to re-engineer the Academic  Development system to provide coherent, effective and sustainable support for students ‘at risk’.
Keywords: academic monitoring; systems thinking; sustainable academic support; higher education